Annual REE Signal of East Asian Winter Monsoon in Surface Seawater in the Northern South China Sea: Evidence From a Century‐Long Porites Coral Record. Issue 2 (5th February 2018) - Jiang, Wei; Yu, Kefu; Song, Yinxian; Zhao, Jian‐xin; Feng, Yue‐xing; Wang, Yinghui; Xu, Shendong; Han, Tao
Abstract: The East Asian winter monsoon (EAWM) plays a significant role in the Asian climate system. However, the scarcity of direct high‐resolution records, especially those covering recent centuries, limits our understanding of monsoonal dynamics. Here we present a reconstruction of annual EAWM strength over the past century and a half using a Porites coral from Yongxing Island in the northern South China Sea (SCS), where the variations in the rare earth element (REE) parameters in surface seawater are dominantly controlled by the input of aeolian dust. Our record indicates that the EAWM strength weakly increased overall during the latter half of the nineteenth century but decreased during the twentieth century, especially after 1950 Common Era. Additionally, during the past century and a half, the relationship between the EAWM and the East Asian summer monsoon, as recorded in speleothems, varied temporally and depended on the strength of the EAWM. Our findings suggest that the REE proxy of corals from the offshore SCS can be applied as an excellent indicator of the winter monsoon strength. Key Points: The contents and patterns of REEs in the surface seawater appear to be largely controlled by aeolian dust The Ce anomaly values of coral can be used as a novel proxy for the strength of the East Asian winter monsoon The relationship between the East Asian winter and summer monsoons varied temporally during the past century and a half